What we learn from China's rising shadow banking: Exploring the nexus of monetary tightening and banks' role in entrusted lending - Kaiji Chen; Jue Ren; Tao Zha (Federal Reserve Bank of Atlanta, 2016)
We argue that China's rising shadow banking was inextricably linked to potential balancesheet risks in the banking system. We substantiate this argument with three didactic findings: (1) commercial banks in general were prone to engage in channeling risky entrusted loans; (2) shadow banking through entrusted lending masked small banks' exposure to balance-sheet risks; and (3) two well-intended regulations and institutional asymmetry between large and small banks combined to give small banks an incentive to exploit regulatory arbitrage by bringing off-balance-sheet risks into the balance sheet. We reveal these findings by constructing a comprehensive transaction-based loan dataset, providing robust empirical evidence, and developing a theoretical framework to explain the linkages between monetary policy, shadow banking, and traditional banking (the banking system) in China.
Keywords: G28; E02; E5; G11; G12; 330; Regulatory arbitrage; asset pricing; institutional asymmetry; entrusted loans; risk taking; shadow loans; bank loans; nonloan investment; nonbank trustees; small banks; large banks; balance sheet; optimal decisions; Informeller Finanzsektor; Bankrisiko; Kreditrisiko; Geldpolitik; Bankenregulierung; Bankrechnungslegung; China